CHANGE OF CONNECTION BETWEEN MAGNETIC PARAMETERS OF CAST IRON IN COMPARISON WITH STEEL UNDER INFLUENCE OF INTERNAL DEMAGNETIZATION - S. G. Sandomirsky (Литьë и металлургия)
Connection of maximum magnetic permeability µm of cast irons with coercive force Нс and residual magnetism Мr is established in all size of changing of the magnetic characteristics of cast iron. Differences of this connection for steels and cast irons are revealed. Formula for calculation µm of steels by Нс and Мr is corrected for calculation µm of cast irons. As a result of correction the calculation error of cast irons µm is diminished. The results can be used in magnetic structural analysis instead of labor-consuming measurement µm.